Composition, structure, and floristic diversity of the dry forest of Agalta Valley, Honduras - Ferrufino-Acosta, Lilian; Cruz, Saby Y.; Mejía-Ordóñez, Thelma; Rodríguez, Fabiola; Escoto, Dorian; Sarmiento, Elia; Larkin, Jeffery L. (Instituto de Ecología, A.C., 2019)
Dry forests are considered one of the most threatened ecosystems in the tropics due to anthropogenic activities that cause fragmentation and habitat loss. Structural and plant composition data were collected from 265 plots in 35 sites, resulting in the identification of 316 species distributed in 76 families and 222 genera, including 79% eudicot, 15% monocot, 8% monilophytes, and 1% gymnosperms. The vertical and horizontal distribution indicated that the forest is dominated by young individuals. Acacia picachensis (Fabaceae), Eugenia hondurensis (Myrtaceae), and Lysiloma acapulcense (Fabaceae) were identified as the most dominant plant species based on the importance value index. The remaining Agalta Valley’s dry forest represents a unique habitat and is the refuge of many native, rare, and endemic species, including some considered high conservation priority.